2016
DOI: 10.1118/1.4948997
|View full text |Cite
|
Sign up to set email alerts
|

Development of a temperature‐controlled phantom for magnetic resonance quality assurance of diffusion, dynamic, and relaxometry measurements

Abstract: The combination of a novel PVP phantom, with multiple compartments to give a physiologically relevant range of ADC and T1 values, together with ice-water as a temperature-controlled medium, allows reliable quality assurance measurements that can be used to measure agreement between MRI scanners, critical in multicenter functional and quantitative imaging studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 32 publications
6
28
0
Order By: Relevance
“…Nonuniform bias was observed when the phantom was rotated every 90°, indicating the magnetic field was not symmetric, but our results show appropriate gradient modeling can account for this. The observed ADC of water at 0°C in our study was (1.12 ± 0.01) ×10 −3 mm 2 /s and is consistent with the ADCs reported by Palacios et al, Easteal et al, Jerome et al, and Hectors et al However, our observed ADC was slightly larger than the ADC established by Holz et al and Chenevert et al but was not statistically different. At 20°C, our mean ADC ([2.04 ± 0.03] ×10 −3 mm 2 s) for water was within 1% of the assumed ground truth ADC (2.023 ×10 −3 mm 2 s) .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nonuniform bias was observed when the phantom was rotated every 90°, indicating the magnetic field was not symmetric, but our results show appropriate gradient modeling can account for this. The observed ADC of water at 0°C in our study was (1.12 ± 0.01) ×10 −3 mm 2 /s and is consistent with the ADCs reported by Palacios et al, Easteal et al, Jerome et al, and Hectors et al However, our observed ADC was slightly larger than the ADC established by Holz et al and Chenevert et al but was not statistically different. At 20°C, our mean ADC ([2.04 ± 0.03] ×10 −3 mm 2 s) for water was within 1% of the assumed ground truth ADC (2.023 ×10 −3 mm 2 s) .…”
Section: Discussionsupporting
confidence: 92%
“…The mean ADCs for various PVP concentrations at 0°C were very similar to results published in the literature (within 2%) except for vials with PVP concentration ≤30%. This was due to a suboptimal imaging protocol for higher PVP concentration vials that have lower diffusivity values that are not well matched to the b‐value used in this study . Studies have shown that the number of b‐values, the selected b‐values, and other scan parameters such as TE affect the overall ADC estimate, particularly for low diffusivity materials .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Many materials have been used in DWI phantoms, such as aqueous solutions of polydimethylsiloxane, polyvinylpyrrolidone, sucrose, or polymers, liquid paraffin, alkanes, and pure water . The aqueous solutions and pure water are good choices for a phantom because of their nontoxicity and availability.…”
Section: Precision Metrologymentioning
confidence: 99%
“…Earlier studies also have shown high similarity between ADC values at both field strengths in a dedicated diffusion phantom (26) and in the abdominal organs (27). In our study, keeping acquisition parameters identical between 1.5 T and 3.0 T, except for differences in TE, was intentional.…”
Section: Discussionmentioning
confidence: 59%